Antibacterial and Anticancer Activities of Acetone Extract Caesalpinia sappan L. - Juwitaningsih, Tita; Syahputra, Nurhadi; Eddiyanto, Eddiyanto; Windayani, Neneng; Rukayadi, Yaya (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Sappan wood (Caesalpinia sappan L.) from the Caesalpiniaceae family is a plant that has been widely used as a health drink such as herbal medicine, in Sundanese called jamu or wedang secang. The drink containing C.sappan extract is traditionally believed to have the ability to reduce symptoms of colds, coughs, canker sores, and rheumatism, overcome fatigue and improve blood circulation. In this research, wood extract of C. sappan L in acetone solvent tested as antibacterial and anticancer. The antibacterial test was performed on the bacteria Streptococcus mutans ATCC 35668 and Enterococcus. faecalis ATCC 49619 with paper disc diffusion method. The microdilution method was used to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The anticancer test is carried out in vitro on A549 lung cancer cells using the MTT method assay. The results showed that the wood extract of C. sappan L in acetone has weak antibacterial activity against S. mutans ATCC 35668 and E. faecalis ATCC 49619. The MIC is 1250 ug/mL, respectively. Aceton wood extract of C. sappan L. showed moderate anticancer activity with IC50 value 90,01Âµg/mL. Thus, the extract of C. sappan L. in acetone has the potential as a source of anticancer compounds.